Aggressive mimicry in a coral reef fish: The prey's view. Issue 23 (20th October 2020) - Pierotti, Michele E. R.; Wandycz, Anna; Wandycz, Pawel; Rebelein, Anja; Corredor, Vitor H.; Tashiro, Juliana H.; Castillo, Armando; Wcislo, William T.; McMillan, W. Owen; Loew, Ellis R.
Abstract: Since all forms of mimicry are based on perceptual deception, the sensory ecology of the intended receiver is of paramount importance to test the necessary precondition for mimicry to occur, that is, model‐mimic misidentification, and to gain insight in the origin and evolutionary trajectory of the signals. Here we test the potential for aggressive mimicry by a group of coral reef fishes, the color polymorphic Hypoplectrus hamlets, from the point of view of their most common prey, small epibenthic gobies and mysid shrimp. We build visual models based on the visual pigments and spatial resolution of the prey, the underwater light spectrum and color reflectances of putative models and their hamlet mimics. Our results are consistent with one mimic‐model relationship between the butter hamlet H. unicolor and its model the butterflyfish Chaetodon capistratus but do not support a second proposed mimic‐model pair between the black hamlet H. nigricans and the dusky damselfish Stegastes adustus . We discuss our results in the context of color morphs divergence in the Hypoplectrus species radiation and suggest that aggressive mimicry in H. unicolor might have originated in the context of protective (Batesian) mimicry by the hamlet from its fish predators rather than aggressive mimicry driven by its prey. Abstract : Hamlets are colour polymorphic reef fishes believed to be diverging by aggressive mimicking of one of a number of unrelated non‐predatory fishes. We study the visual system of the intended receiver of hamlets' mimicry, their prey, and test whether model‐mimic mis‐identification by the prey is likely to occur. We find that only one hamlet is likely to be an efficient mimic in the eyes of their prey but we observe that the mimic colour morph might in fact have evolved by Batesian mimicry first and only subsequently recruited for aggressive mimicry.